The rule of a geometric sequence:
![a_n=a_1r^{n-1}](https://tex.z-dn.net/?f=a_n%3Da_1r%5E%7Bn-1%7D)
We have:
![a_1=6;\ r=-\dfrac{1}{3}](https://tex.z-dn.net/?f=a_1%3D6%3B%5C%20r%3D-%5Cdfrac%7B1%7D%7B3%7D)
Find ![a_8=?\to n=8](https://tex.z-dn.net/?f=a_8%3D%3F%5Cto%20n%3D8)
substitute:
![a_8=6\cdot\left(-\dfrac{1}{3}\right)^{8-1}=6\cdot\left(-\dfrac{1}{3}\right)^7=6\cdot\left(-\dfrac{1}{2187}\right)=-\dfrac{2}{729}](https://tex.z-dn.net/?f=a_8%3D6%5Ccdot%5Cleft%28-%5Cdfrac%7B1%7D%7B3%7D%5Cright%29%5E%7B8-1%7D%3D6%5Ccdot%5Cleft%28-%5Cdfrac%7B1%7D%7B3%7D%5Cright%29%5E7%3D6%5Ccdot%5Cleft%28-%5Cdfrac%7B1%7D%7B2187%7D%5Cright%29%3D-%5Cdfrac%7B2%7D%7B729%7D)
Step-by-step explanation:
<h2>
Sum of two complementary angle is 90°</h2><h2 /><h2>
so. </h2><h2>
<R+<S =90°</h2><h2>
12x-3+7x-2=90°</h2><h2>
19x-5=90°</h2><h2>
19x=95°</h2><h2>
X= 5</h2>
<h2>
<R= 60-3=57°</h2>
Answer:
−
6
=
3
7
n
Step-by-step explanation:
Rewrite the equation as
3
7
n
=
−
6
.
3
7
n
=
−
6
Multiply both sides of the equation by
7
3
.
7
3
⋅
3
7
⋅
n
=
7
3
⋅
−
6
Simplify both sides of the equation.
Tap for more steps...
n
=
−
14